Respostas

2013-08-10T18:59:38-03:00
A=(2x +6).(x-2).(x-1)
a= (2x + 6).(x-2)
a= (2x² + 4x + 6x - 12) .(x-1)
a= (2x² +10x -12) .(x-1)
a= 2x³ -2x² + 10x² - 10x -12x +12
a= 2x³ +8x² -22x +12

b=(x-1).(x-2)
b= x² -2x -x + 2
b= x² -3x + 2

Subtração dos polinômios                             Adição dos polinômios

(2x³+8x² -22x +12) - (x² - 3x +2)         (2x³ +8x² - 22x + 12) + (x² -3x +2)
2x³ + 8x² - 22x + 12 - x² + 3x- 2         2x³ + 8x² -22x+ 12 +x² -3x +2
2x³ +7x² -19x + 10                             2x³ + 9x² -25x +14